Conference on “Consequences of Sentences of the Constitutional Tribunal in the Light of the Decisions Taken by the Supreme Administrative Court, the Supreme Court and the Constitutional Tribunal” (Ius Novum, 2013)
Konferencja na temat: „Skutki wyroków Trybunału Konstytucyjnego w świetle orzecznictwa naczelnego Sądu Administracyjnego, Sądu Najwyższego i Trybunału Konstytucyjnego”